PENGARUH TERAPI ASMAUL HUSNA DENGAN KOMBINASI SLOW DEEP BREATHING TERHADAP TINGKAT KECEMASAN MENGHADAPI KEMATIAN PADA LANJUT USIA DI POSYANDU LANSIA DUSUN KERTO KIDUL PLERET BANTUL YOGYAKARTA - Nasrul Hakim; Peggy Yolanda Savitri (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2018)
Background: Elderly people spend much time to think about death compared to individuals who are still young. Pondering and planning death are normal parts of the life of the elderly (Sheila L. Videbeck, 2008). Spirituality greatly affects anxiety over death. The spiritual and physical effort that can be done to reduce excessive anxiety is to carry out Asma'ul Husna therapy with a combination of slow deep breathing.  Objective: To determine the effect of Asma'ul Husna therapy with a combination of slow deep breathing to the level of anxiety facing death in the elderly at the Elderly Posyandu in Kerto Kidul Village, Bantul Pleret Village, Yogyakarta.  Methods: This type of research is a quasi-experimental design with one group pretest-posttest design, intervention 3 times for 1 week. The activity begins with a pre-test of measuring anxiety facing death using the ZSAS / ZSRAS questionnaire. then the post test was carried out on the third day after the treatment was completed. A sample of 32 respondents who were active in the elderly yandu post. Test statistical analysis using the Paired t-Test.  Results: the result of this research shows that Asymp. Sig (2-tailed) is 0,000 (p value), so p 0.05. then the hypothesis is (Ho) is rejected and the hypothesis (Ha) is accepted.  Conclusion: There is a significant effect after being given Asma'ul Husna Therapy with a combination of slow deep breathing to the level of anxiety facing death in the elderly at the Posyandu in Kerto Kidul Hamlet, Pleret Bnatul Yogyakarta.